PERANCANGAN SISTEM INFORMASI RESEPSIONIS PADA DINAS PERPUSTAKAAN DAN KEARSIPAN KOTA PALEMBANG - Haski, Didi Putra; Agiyani, Gina (LPPM Universitas Putera Batam, 2025)
This research aims to design a receptionist information system at the Palembang City Library and Archives Office to facilitate visitor registration and data management. The system is designed to enhance operational efficiency and improve service quality for visitors. Using the Prototype development model, the system goes through the stages of requirement analysis, design, implementation, and testing. The research results show that the developed system improves visitor management with features such as digital registration, data recapitulation, and data export to Excel format. Additionally, the system supports library operations by accelerating data retrieval and generating more structured reports. The implementation of this system is expected to accelerate digital transformation in library administration and enhance service quality for the public.